Enablers and Barriers to Successful Implementation of Cooperative Learning through Professional Development - Mohamed Alansari; Christine Margaret Rubie-Davies (MDPI AG, 2021)
Literature shows cooperative learning has positive benefits for students' learning and social outcomes. Even though cooperative learning studies have been conducted in all areas of the curriculum, few studies have investigated whether there are similar effects for students across several curriculum areas or age groups. Moreover, less attention has been given to how professional learning and development (PLD) opportunities can contribute to changes in instructional practice. We illustrate how research on cooperative learning can be translated into practice, through a one-year University-School partnership. The current study is focused on our PLD work in one large private school based in New Zealand. Analysis of school data (quantitative student data and qualitative teacher data) indicated that, by the end of the school year, students reported experiencing more cooperative learning opportunities in their classes. Teachers believed that the PLD supported change in their practice and noted positive changes in student engagement. Analysis of student data also revealed differential outcomes by subject and age group. Overall, our study showed that PLD opportunities can contribute to the successful implementation of cooperative learning.